Management of nursing care in HIV/AIDS from a palliative and hospital perspective - Karen Gisela Moraes Zepeda; Marcelle Miranda da Silva; Débora Cristina Leitão dos Santos; Rafael Barroso Gaspar; Liana Amorim Corrêa Trotte
ABSTRACT Objectives: To understand the meaning attributed by the nurse to the management of nursing care to the person hospitalized due to clinical complications caused by AIDS; to analyze actions related to palliative care; and to construct a theoretical matrix regarding the management of nursing care. Method: Qualitative, exploratory research, guided by the Grounded Theory. Seven nurses and ten nursing technicians were interviewed between May and September 2015, in a university hospital, located in Rio de Janeiro State, Brazil. Results: Five categories that covered the profile of the hospitalized person, palliative care, intervening conditions for care management, the need for professional qualification, and other aspects to better organize and manage care, including conflict management arose. Final considerations: The theoretical matrix values the quality of life, the need to understand the flow of care to avoid readmissions and not adherence to medications, requiring new research in the area, such as implementation.